Toward Formal Models and Languages for Verifiable Multi-Robot Systems - De Nicola, Rocco; Di Stefano, Luca; Inverso, Omar (Frontiers in Robotics and AI, 2018)
Incorrect operation of a Multi-Robot System (MRS) may not only lead to unsatisfactory results, but can also cause economic losses and jeopardize safety. These risks may not always be evident since they may arise as unforeseen consequences of interactions between different components of the system. Thus, tools and techniques that can help in providing guarantees about the behaviour of MRSs are on demand; and, whenever possible, these guarantees should be backed up by formal proofs complementing traditional approaches based on testing and simulation. Tailored linguistic support to specify MRSs is a major step towards this goal. Indeed, reducing the gap between typical features of an MRS and the linguistic primitives used to model them would simplify both the specification of these systems and their verification. With the aim of reducing this gap, in this work we identify some key features of MRSs. Then we consider a selection of three specification languages oriented towards MRSs, representative of wider categories of languages with similar aims. We finally assess the extent to which the considered languages capture the key features in an adequate and intuitive way by using them to implement MRSs case studies.